New efficient designs of reversible logic gates and circuits in the QCA technology - Rezaei, Abbas (Array, 2019)
Quantum-dot cellular automata (QCA) is a developing nanotechnology, which seems to be a good candidate to replace the conventional complementary metal-oxide-semiconductor (CMOS) technology. The QCA has the advantages of very low power dissipation, faster switching speed, and extremely low circuit area, which can be used in designing nanoscale reversible circuits. In this paper, the new efficient QCA implementations of the basic reversible Gates such as: CNOT, Toffoli, Feynman, Double Feynman, Fredkin, Peres, MCL, and R Gates are presented based on the straight interactions between the QCA cells. Also, the designs of 4-Bit reversible parity checker and 3-bit reversible binary to Grey converter are introduced using these optimized reversible Gates. The proposed layouts are designed and simulated using QCADesigner software. In comparison with previous QCA designs, the proposed layouts are implemented with the minimum area, minimum number of cells, and minimum delay without any wire-crossing techniques. Also, in comparison with the CMOS technology, the proposed layouts are more efficient in terms of the area and power. Therefore, our designs can be used to realize quantum computation in ultralow power computer communication.